2014
DOI: 10.1007/s12011-014-9918-6
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Induces PC12 Cells Apoptosis via an Extracellular Signal-Regulated Kinase and c-Jun N-Terminal Kinase-Mediated Mitochondrial Apoptotic Pathway

Abstract: To investigate the role of mitogen-activated protein kinase (MAPK) and downstream events in cadmium (Cd)-induced neuronal apoptosis executed via the mitochondrial apoptotic pathway, this study used the PC-12 cell line as a neuronal model. The result showed that Cd significantly decreased cell viability and the Bcl-2 / Bax ratio and increased the percentage of apoptotic cells, release of cytochrome c, caspase-3, and poly(ADP-ribose) polymerase cleavage, and nuclear translocation of apoptosis-inducing factor (AI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 37 publications
4
30
0
Order By: Relevance
“…We detected the changes of MAPK signaling pathways, and found that ERK, p38 and JNK cascades were phosphorylated and activated in the cadmium-treated PC12 cells. Similar results were observed that activation ERK and JNK mediated a caspase-dependent pathway in cadmium induced PC12 cells and primary rat cerebral cortical neurons apoptosis [15,46]. L-Theanine suppresses ERK/ p38 kinase and NF-jB pathways to attenuate Ab-induced cognitive dysfunction and neurotoxicity [47].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…We detected the changes of MAPK signaling pathways, and found that ERK, p38 and JNK cascades were phosphorylated and activated in the cadmium-treated PC12 cells. Similar results were observed that activation ERK and JNK mediated a caspase-dependent pathway in cadmium induced PC12 cells and primary rat cerebral cortical neurons apoptosis [15,46]. L-Theanine suppresses ERK/ p38 kinase and NF-jB pathways to attenuate Ab-induced cognitive dysfunction and neurotoxicity [47].…”
Section: Discussionsupporting
confidence: 78%
“…#P \ 0.05 versus Cd alone implicated in mitochondrial-dependent apoptosis. Cadmium affects a number of signaling cascades [15][16][17]. Western blot analysis also revealed that the levels of p-PI3K and p-Akt were higher in cadmium group than in the control group, L-theanine pretreatment significantly reduced the levels of p-PI3K and p-Akt to 1.01 ± 0.1, 2.65 ± 0.1-fold of control, respectively.…”
Section: L-theanine Decreased Erk/jnk Signaling Pathwaymentioning
confidence: 99%
“…We have previously shown that Cd induces ERK activation in differentiated Caco‐2 cells, but not in undifferentiated cultures with a clear correlation with an increase in MTT‐reducing activity . Many studies have shown that 1 to 10 µM Cd may rapidly increase ERK1/2 phosphorylation, but very few have already reported a correlation between the level of ERK phosphorylation and that of MTT‐reducing activity . Because of the large use of the MTT assay, especially in toxicology and pharmacology, the link between these parameters in nonproliferative cells deserves to be further investigated.…”
Section: Resultsmentioning
confidence: 99%
“…In neuronal (PC12 and SH-SY5Y) cells, cadmium-induced intracellular Ca 2+ elevation, leading to cell apoptosis, is due to activation of the MAPK and mTOR signaling pathways through stimulation of phosphorylation of JNK, Erk1/2, p38 MAPK, mTOR and calcium/calmodulin (CaM)-dependent protein kinase II (CaMKII) [16,[21][22][23]. The elevation of intracellular Ca 2+ could activate CaM.…”
Section: Mechanisms Of Ca 2+ Overload-mediated Cell Apoptosis Inducedmentioning
confidence: 99%